Early reduction of acute anterior shoulder dislocations in a ski field setting. (16th March 2022) - Fraser, Calum; Pellatt, Richard; Shirran, Mark; McKay, Glenn; Smith, Michael
Abstract: Objective: The present study describes the management of suspected shoulder dislocations in ski field clinics. Methods: Data were collected from two clinics in Queenstown, New Zealand. Suspected anterior shoulder dislocations, with no suspicion of significant fractures and without imaging, underwent attempted reduction. Results: Ninety percent ( n  = 49) of dislocations were successfully relocated. No short‐term complications because of this procedure were observed. Conclusion: This short report raises the possibility that early anterior shoulder reduction in a ski field clinic can be safe without imaging, in select cases. Prospective studies including patient centred data are recommended.